Penerapan Sistem Silvikultur Tebang Pilih Tanam Indonesia (TPTI) pada Hutan Dipterocarpaceae, Hutan Hujan Dataran Rendah di HPH PT. Hugurya, Aceh - Indrawan, Andry (Jurnal Manajemen Hutan Tropika, 2002)
The study describes the implementation of the sylviculture system of Indonesian selective logging and planting (TPTI) in lowland tropical forest. The study area, which is located in the forest concession area of PT. Hugurya (Aceh), is dominated by species of kapur (Dryobalanops aromatica) and meranti (Shorea leprosula). Within the study area, tree species currently exploited include Shorea leprosula, Dryobalanops aromatica, Dipterocarpus grandtjlorus (Dipterocarps family), and Scapium macropudum (Sterculiaceae family). The species in tree and regeneration stages that were found either in primary forest or logged-over forest are dominated by commercial species, especially tree species from the Dipterocarps family. The number of nucleus trees (seed trees) is sufficient and fulfills the requirement of Indonesian selective cutting and planting. The condition of natural regeneration is also sufficient and will ensure the forest's sustainability at the next cutting cycle.